(untitled) (Indo-MathEdu Intellectuals Journal, 2025)
This study examines the case of students’ lack of awareness of social responsibility encountered in one of the students at the high school level who is the subject of this study. The subject was a 16-year-old female adolescent who experienced problems in arranging extracurricular schedules and doing schoolwork on time. Complaints prompted researchers to look for alternative treatments for how to manage extracurricular schedules and do assignments so that they do not collide with each other when they want to do it and on time. The alternative chosen by the researcher is to provide the application of self-management techniques to the gestalt approach. The method used in this study is Literature Systematic Review (LSR). The results of this study show that the influence of the application of self-management techniques on the gestalt approach is very effective in increasing students’ awareness of social responsibility.